86.5k views
4 votes
X^2 - 6x + 1 = 0 by completing the square​

User Minding
by
4.5k points

2 Answers

4 votes

Answer:


x = - 2 √(2) + 3 \\ or \\ x = 2 √(2 ) + 3

X^2 - 6x + 1 = 0 by completing the square​-example-1
User Ptrin
by
4.5k points
3 votes

Answer:

See below.

Explanation:

x^2 - 6x + 1 = 0

x^2 - 6x = -1

We halve the coefficient of x (which is -6/2 = -3) and square it, then add this to both sides:-

x^2 - 6x + (-3)^2 = -1 + (-3)^2

x^2 - 6x + 9 = -1 + 9

(x - 3)^2 = 8

x - 3 = ±√8

x = 3 ± √8

= 0.17, 5.83 to 2 decimal places.

User Basanta
by
4.9k points